Răspuns :
Deci ai [tex]9^{x}
[/tex]-[tex]3^{x+1}[/tex] +[tex] \frac{8}{9} [/tex]=0
Rescriem ecuatia: [tex]3^{2x}[/tex]- [tex]3^{x}[/tex] ·3 + [tex] \frac{8}{9} [/tex]=0
Notez [tex]3^{x}[/tex] cu t.
Ecuatia devine t²-3t+[tex] \frac{8}{9} [/tex]=0 | *9 => 9t²-27t+8=0
Δ=[tex]b^{2} [/tex]-4ac= [tex]27^{2} [/tex]- 4·9·8=729-288=441=>
=> √Δ=21
Deci, [tex]t_{1} [/tex]=[tex] \frac{-b+ \sqrt{delta} }{2a} [/tex]= [tex] \frac{27+21}{18} [/tex]=48
si [tex]t_{2} [/tex]=[tex] \frac{-b- \sqrt{delta} }{2a} [/tex]=[tex] \frac{27-21}{18} [/tex]=[tex] \frac{6}{18} [/tex]=[tex] \frac{1}{3} [/tex]
Pentru t=48=> [tex] 3^{x} [/tex]=48 => x=[tex] \sqrt[3]{48} [/tex]= 2[tex] \sqrt[3]{6} [/tex]
Pentru t= [tex] \frac{1}{3} [/tex] => [tex] 3^{x} [/tex]=[tex] \frac{1}{3} [/tex] =>
=> [tex] 3^{x} [/tex]=[tex] 3^{-1} [/tex] => x=-1
Sper ca ti-am fost de ajutor. :)
Rescriem ecuatia: [tex]3^{2x}[/tex]- [tex]3^{x}[/tex] ·3 + [tex] \frac{8}{9} [/tex]=0
Notez [tex]3^{x}[/tex] cu t.
Ecuatia devine t²-3t+[tex] \frac{8}{9} [/tex]=0 | *9 => 9t²-27t+8=0
Δ=[tex]b^{2} [/tex]-4ac= [tex]27^{2} [/tex]- 4·9·8=729-288=441=>
=> √Δ=21
Deci, [tex]t_{1} [/tex]=[tex] \frac{-b+ \sqrt{delta} }{2a} [/tex]= [tex] \frac{27+21}{18} [/tex]=48
si [tex]t_{2} [/tex]=[tex] \frac{-b- \sqrt{delta} }{2a} [/tex]=[tex] \frac{27-21}{18} [/tex]=[tex] \frac{6}{18} [/tex]=[tex] \frac{1}{3} [/tex]
Pentru t=48=> [tex] 3^{x} [/tex]=48 => x=[tex] \sqrt[3]{48} [/tex]= 2[tex] \sqrt[3]{6} [/tex]
Pentru t= [tex] \frac{1}{3} [/tex] => [tex] 3^{x} [/tex]=[tex] \frac{1}{3} [/tex] =>
=> [tex] 3^{x} [/tex]=[tex] 3^{-1} [/tex] => x=-1
Sper ca ti-am fost de ajutor. :)